Pengembangan Media Pembelajaran IPA Berbasis Multimedia Interaktif Pada Materi Energi Alternatif di Kelas IV SD N Sebagai Bentuk Persiapan Pembelajaran Virtual - Anisa Purnama Sari; Dalifa Dalifa; Feri Noperman (Universitas Bengkulu, 2021)
The purpose of this study is to produce Science learning media based interactive multimedia on alternative energy materials in grade IV SD as a form of virtual learning preparation. This research type is a Research and Development (R&D) by modifying the Waterfall model. However, this research was only carried out until the fourth stage, until the testing stage. The testing process is carried out by conducting expert validation and small group testing (teacher and student responses). This media was validated by curriculum experts who were then revised and then responded to by 6 teacher respondents and 6 student respondents. The data analysis technique used descriptive statistical analysis of the results of expert validation and small group testing (teacher and student responses) and qualitative descriptive analysis of comments from expert validation and small group testing (teacher and student responses). This study produces science learning media based interactive multimedia on alternative energy materials as a form of virtual learning preparation, with the percentage of validation results from curriculum experts of 94.5% in the very valid category, the percentage of teacher responses of 97% in the very good category, and the results of student responses. of 96.6% in the very good category. So, from the research that has been carried out, it can be concluded that the science learning media based interactive multimedia on alternative energy materials in grade IV SD can be categorized as a very good learning media and can be used in virtual learning.Keywords: Development, Learning Media, Interactive Multimedia,Virtual Learnin